„Nur manchmal in Theatern springt es uns entgegen“: Ernst Toller’s involvement in the Munich Räterepublik (1919) as ‚realized‘ utopia and its influence on his drama Masse Mensch - Mionskowski, Alexander (Literatūra, 2016)
My article gives a description of political thought included in Toller’s play Masse Mensch (1921) and the government-conceptions it contains. The analysis tries an approach on that problem focusing the historic prototype of Tollers main character Sonja Irene L. and her connection towards Eisner, Landauer and Toller. Another keystone of analysis is the look on Max Weber’s “Herrschaftssoziologie” which Toller probably knew, as he verifiable had contact to the Sociologist from 1917 on and some intensive discussions concerning the German future. Based on Weber’s categories and some ‘laws’ of the revolutionary principle ‘invented’ by Landauer, it explores the political implements of the dramatic constellation and Toller’s aesthetics. The conclusions point out the political positions of the three main actors and Toller’s pedagogical intentions towards the audience – arguing for a behaviour of a “‘nevertheless’ – although ‘I would prefer not to’”.